Relationship Between Knowledge Level and Adolescent Dietary Patterns To Improve Nutritional Status At Pondok Hisbah Al-Fatih Sintang Regency In 2025 - Miftah Chairunnisa; Asri Fitri Yati; Khairulisni Saniati; Arum Seftiani Lestari; Hearty Efifania Ose Payon (Journal of Educational Innovation and Public Health, 2025)
According to the World Health Organization (WHO), good nutritional status during adolescence plays an important role in determining health and quality of life in adulthood. The prevalence of adolescents with poor nutritional status reaches 9.2%, while the prevalence of obesity in adolescents increases to 8.3%. This study aims to determine the relationship between the level of knowledge and adolescent diet patterns to improve nutritional status in Sintang Regency. Cross Sectional research design . The population is adolescents at the Al-Fatih Hisbah Boarding School, Sintang Regency, Kalimantan. Respondents numbered 39 people who were taken by Simple Random Sampling . The study was conducted in December 2024. The results of the study obtained a p value of 0.026 ≤ 0.05, meaning that there is a relationship between the level of knowledge and adolescent diet patterns at the Al-Fatih Hisbah Boarding School, Sintang Regency. Health workers are expected to increase educational activities for adolescents regarding healthy diets .